Acetate: Friend or foe against breast tumour growth in the context of obesity?. Issue 24 (26th October 2020) - Yelek, Caner; Mignion, Lionel; Joudiou, Nicolas; Terrasi, Romano; Gourgue, Florian; Van Hul, Matthias; Delzenne, Nathalie; Gallez, Bernard; Corbet, Cyril; Muccioli, Giulio G.; Feron, Olivier; Cani, Patrice D.; et al.
Abstract: Acetate is reported as a regulator of fat mass but also as lipogenic source for cancer cells. Breast cancer is surrounded by adipose tissue and has been associated with obesity. However, whether acetate contributes to cancer cell metabolism as lipogenic substrate and/or by changing fat storage and eventually obesity‐induced breast cancer progression remains unknown. Therefore, we studied the contribution of acetate to breast cancer metabolism and progression. In vitro, we found that acetate is not a bioenergetic substrate under normoxia and did not result in a significant change of growth. However, by using lipidomic approaches, we discovered that acetate changes the lipid profiles of the cells under hypoxia. Moreover, while mice fed a high‐fat diet (HFD) developed bigger tumours than their lean counterparts, exogenous acetate supplementation leads to a complete abolishment of fat mass gain without reverting the HFD‐induced obesity‐driven tumour progression. In conclusion, although acetate protects against diet‐induced obesity, our data suggest that it is not affecting HFD‐driven tumour progression.